Recent violence and legal involvement among young adults with early psychosis enrolled in Coordinated Specialty Care. Issue 4 (9th May 2018) - Rolin, Stephanie A.; Marino, Leslie A.; Pope, Leah G.; Compton, Michael T.; Lee, Rufina J.; Rosenfeld, Barry; Rotter, Merrill; Nossel, Ilana; Dixon, Lisa
Abstract : Aim: Individuals with serious mental illnesses have a small increased risk of engaging in violence or legal involvement compared to the general population. This seems to be particularly true for young adults experiencing early stages of psychosis. This study analysed the prevalence of and risk factors for reports of violence and legal involvement in a sample of young adults receiving Coordinated Specialty Care for early non‐affective psychosis. Methods: A total of 373 young adults (ages 16‐30) within 2 years of the onset of non‐affective psychosis were enrolled in 10 Coordinated Specialty Care sites in New York State from October 2013 to August 2016. Baseline violent ideation or behaviour and legal involvement was described and predictors identified. Results: Approximately one‐quarter of individuals had either recent violent ideation or behaviour at baseline ( n = 90, 24.6%); nearly one‐tenth of the sample reported recent legal involvement ( n = 33, 9.0%). Individuals with violent ideation or behaviour had lower levels of education and were less likely to be working. Those with recent legal involvement were more likely to be male and more likely to have substance use (alcohol, cannabis and other drugs). Conclusions: The overall rate of recent violent ideation or behaviour is similar to other studies; up to one‐third of individuals experiencing a first‐episode of psychosis (FEP) report violence. Recent legal involvement was strongly associated with substance use. This study presents insight into violence and legal involvement among individuals with FEP and indicates the need for further research.